(untitled) (Third Sector Social Economic Review, 2025)
The global digitalization process has led to the emergence of various management approaches. One such approach is reverse mentoring. Reverse mentoring involves a less experienced, younger employee providing technological literacy to an older leader. Through this practice, employees have the opportunity to establish a close relationship with leaders, gaining recognition and respect. The more experienced mentors can gain insights into the perspectives of their mentees, which may enhance commitment and collaboration. The primary aim of this study is to investigate whether transformational leadership serves as a mediating role in the impact of reverse mentoring on emotional commitment. The research dataset consists of 332 surveys collected from bankers in the finance sector and academics in the education sector in Ankara, Istanbul, and Izmir. SPSS software was utilized for data entry and analysis. The study employed validity and reliability tests, Pearson correlation, simple linear and multiple regression analyses, as well as Process Macro analysis to identify the mediating variable. According to the results, a relationship was identified among reverse mentoring, emotional commitment, and transformational leadership from the perspective of the participants. Additionally, transformational leadership was found to mediate the relationship between reverse mentoring and emotional commitment.